Credit Card Cue Effect: Debt-Related Thought as Mediating Variable of Credit Card Cues and Spending - Agustion Suhada; Taufik Faturohman (UNIVED Press, 2024)
This study aims to examine the relationship between credit card cues, credit card associations (especially debt-related thought), and spending behavior in Indonesia. The data were collected through an online survey with 400 respondents and analyzed using PLS-SEM. The result showed that credit card cue has significant positive correlation to debt-related thought. Debt-related thought has no significant correlation to spending. Credit card cue has significant positive correlation to spending. Debt-related thought is not able to moderate credit card cues on spending which refers to direct only mediation.